Visão computacional no auxílio de deficientes visuais - Mendonça, André H. L. de (Universidade Federal Rural do Semi-Árido, 2019)
This article discusses problems that people with visual impairment face in their daily lives and how assistive technologies can help them overcome those problems. Aiming to assist visually impaired people with a specific problem, a Real bill identifier has been developed. The algorithm uses SIFT (Scale Invariant Feature Transform) to extract features from an image and to create their descriptors. A logic to use the generated descriptors to identify the bills was used, and the algorithm acquired good results, with a relatively low error rate
Artigo Acadêmico
Keywords: Deficientes visuais; Visão computacional; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO